ANALISIS TAFSIR AL-KASYSYĀF KARYA AL-ZAMAKHSYARI: KONTEKS SEJARAH, PENDEKATAN, DAN CORAK PENAFSIRAN - Surya, Ilham; Wahyuni, Sri (Ma'had Aly As'adiyah Sengkang, 2025)
This study aims to examine Tafsir Al-Kasysyāf from the perspectives of the author's background, content analysis, and the interpretive dynamics of his time. It is a qualitative study employing a literature-based approach. The primary data source for this research is the exegetical work Al-Kasysyāf ʿan Ḥaqāʾiq Ghawāmiḍ Al-Tanzīl by Imam Al-Zamakhshari. In addition, the study draws on various historical texts, particularly those containing commentaries on Al-Kasysyāf and the historical context surrounding its composition. The findings of this study indicate that Tafsir Al-Kasysyāf represents a rich intellectual legacy and may serve as a valuable reference in the field of Qur’anic exegesis generally, and specifically for understanding the Muʿtazilite school of thought in a comprehensive and objective manner.Keywords: Al-Kasysyāf, Al-Zamakhsyari, Mu’tazilite